Site- and phase-selective x-ray absorption spectroscopy based on phase-retrieval calculation. (7th February 2017) - Kawaguchi, Tomoya; Fukuda, Katsutoshi; Matsubara, Eiichiro
Abstract: Understanding the chemical state of a particular element with multiple crystallographic sites and/or phases is essential to unlocking the origin of material properties. To this end, resonant x-ray diffraction spectroscopy (RXDS) achieved through a combination of x-ray diffraction (XRD) and x-ray absorption spectroscopy (XAS) techniques can allow for the measurement of diffraction anomalous fine structure (DAFS). This is expected to provide a peerless tool for electronic/local structural analyses of materials with complicated structures thanks to its capability to extract spectroscopic information about a given element at each crystallographic site and/or phase. At present, one of the major challenges for the practical application of RXDS is the rigorous determination of resonant terms from observed DAFS, as this requires somehow determining the phase change in the elastic scattering around the absorption edge from the scattering intensity. This is widely known in the field of XRD as the phase problem. The present review describes the basics of this problem, including the relevant background and theory for DAFS and a guide to a newly-developed phase-retrieval method based on the logarithmic dispersion relation that makes it possible to analyze DAFS without suffering from the intrinsic ambiguities of conventional iterative-fitting. Several matters relating to data collection and correction of RXDS are also covered, with a final emphasis on the great potential of powder-sample-based RXDS (P-RXDS) to be used in various applications relevant to practical materials, including antisite-defect-type electrode materials for lithium-ion batteries.